Trap assisted visible light luminescent properties of hydrothermally grown Gd doped ZnO nanostructures. (January 2021) - Malik, Khurshaid Ahmad; Malik, Javied Hamid; Bhat, Aadil Ahmad; Assadullah, Insaaf; Tomar, Radha
Abstract: Pristine ZnO and Gd-doped ZnO nanostructures were synthesized via the hydrothermal route to study the influence of Gd doping on the growth and properties of the nanostructures. Synthesized nanostructures were characterized by powder x-ray diffraction technique (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDS) and UV–visible spectroscopy. Optical study demonstrated that the nanostructures exhibit good visible light transmittance and absorbs ultraviolet light energy. Photoluminescence (PL) study of the nanostructures showed that Gd-doping enhanced the PL activity of the nanostructures by possible introduction of the defect levels. The corresponding augmentation in PL intensity (visible light luminescent intensity) is attributed to comparative increase in crystallinity, complex defects (traps) and electron hole pair recombination rate. This enhanced luminescent property of Gd-doped ZnO nanostructures can be exploited for the luminescence based applications like sensors, UV-Lasers, phosphors, LEDs, luminescent biolabels, etc. Highlights: Synthesis of pristine ZnO and Gd-doped ZnO nanostructures via hydrothermal route. X-ray diffraction technique showed that incorporation of Gd 3+ ions as dopant does not alter the crystal structure but introduces only a slight variation in lattice parameters as reflected by a slight shift in peak positions. Photoluminescent measurements showed that the intensity of the emission Peaks (particularly at 650 known as orange red emission) gets enhanced as the concentration of Gd 3+ ions in the nanostructures increases.